2014
DOI: 10.5534/wjmh.2014.32.3.133
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Long-Term Daily Dosage of Alfuzosin 10 mg upon Sexual Function of Benign Prostatic Hypertrophy Patients: Two-Year Prospective Observational Study

Abstract: PurposeTo identify sexual function improvement associated with alfuzosin (10 mg daily for 2 years).Materials and MethodsWe enrolled 30 men with lower urinary tract symptom (LUTS) who visited Gyeongsang National University Hospital between 2010 and 2012. At first visit, urinalysis, prostate specific antigen, transrectal ultrasound, and uroflowmetry were performed. The nternational Prostate Symptom Score (IPSS), quality of life (QoL), International Index of Erectile Function (IIEF), and Male Sexual Health Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…Previous studies have shown the sensitivity of total MSHQ scale scores to both diagnostic status and treatment conditions . The ejaculation domain subscale of the MSHQ has shown treatment sensitivity to pharmacological and other treatments of BPH , although a minimum clinically meaningful change in ejaculation has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the sensitivity of total MSHQ scale scores to both diagnostic status and treatment conditions . The ejaculation domain subscale of the MSHQ has shown treatment sensitivity to pharmacological and other treatments of BPH , although a minimum clinically meaningful change in ejaculation has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…MSHQ-EjD and IPSS were measured at baseline and after treatment was commenced, however follow-up time varied. All trials were conducted over multiple centres across Asia with the exception of Yoon et al [ 15 ]. Individual sample sizes varied with largest trial in Tunisia assessing 730 patients [ 16 ], while the others had less than 200 patients each.…”
Section: Resultsmentioning
confidence: 99%
“…A number of similarities between these studies regarding patient selection criteria, intervention protocol and outcomes measured was observed. Kim et al [ 17 ] had the shortest intervention time, re-assessing men after just 3 months of treatment, while Yoon et al [ 15 ] followed their patients up to 2 years after commencement of treatment. In addition to the above six papers, Martín-Morales et al [ 18 ] also met inclusion criteria, however published data was incomplete.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding ejaculation‐related SexAEs, most patients across both treatment groups reporting these SexAEs had worsening MSHQ ejaculation domain scores at month 12. The ejaculation domain subscale of the MSHQ has shown treatment sensitivity to pharmacological and other treatments of BPH, although a minimum clinically meaningful change in ejaculation has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%